Application of Curriculum of Silsilah Quranuna with Numerical and Language Approach in Ibadurrahman Islamic Boarding School - Qodir Thohir, Syahid Abdul; Romadoni, Amma Muliya; Mardani, Dede Aji (Jurnal Pendidikan Tambusai, 2021)
Studying the Quran is an obligation as a Muslim. There are many methods and ways to learn the Quran, from improving reading (Tahsin), memorizing (Tahfizh), or understanding. However, it is a very rare integration between the Quran with the other lessons. Silsilah Quranuna (SQ) is a method compiled from the ground up to read, memorize, and understand Quran based on tajwid, language, and mathematics rules. SQ method is specially prepared based on approaches of numerical and language as the basis of science. SQ curriculum included preparation for reading the Quran from primary to memorization by integrating other subjects, such as with mathematics and languages (Arabic and English). This study aims to compare the Quran method that applied at Ibadurrahman Islamic boarding school in Tasikmalaya. The research method was qualitative by conducting interviews with several informants and analyzing reports on the sustainability of the Quran program. Based on the study results, it can be concluded that the SQ curriculum provides improvements in terms of administration and integration of Quran lessons, especially the memorizing of the Quran program and language. The method applied previously was not optimal, and there was no integration adjustment to support other lessons.